Associations of the BDNF Val66Met Polymorphism With Body Composition, Cardiometabolic Risk Factors, and Energy Intake in Youth With Obesity: Findings From the HEARTY Study - Goldfield, Gary S.; Walsh, Jeremy; Sigal, Ronald J.; Kenny, Glen P.; Hadjiyannakis, Stasia; De Lisio, Michael; Ngu, Mathew; Prud’homme, Denis; Alberga, Angela S.; Doucette, Steve; Goldfield, Diana B.; Cameron, Jameason D. (Frontiers in Neuroscience, 2021)
The brain-derived neurotrophic factor (BDNF) Val66Met polymorphism is functionally related to BDNF, and is associated with obesity and metabolic complications in adults, but limited research exists among adolescents. This study comparatively examined carriers and non-carriers of the BDNF Val66Met polymorphism on body composition, energy intake, and cardiometabolic profile among adolescents with obesity. The sample consisted of 187 adolescents with obesity; 99 were carriers of the homozygous Val (G/G) alleles and 88 were carriers of the Val/Met (G/A) or Met (A/A) alleles. Cardiometabolic profile and DNA were quantified from fasted blood samples. Body composition was assessed by magnetic resonance imaging (MRI). Compared to carriers of the homozygous Val (G/G) allele, carriers of the Val/Met (G/A) or Met/Met (A/A) variants exhibited significantly higher protein (p = 0.01) and fat (p = 0.05) intake, C-Reactive protein (p = 0.05), and a trend toward higher overall energy intake (p = 0.07), fat-free mass (p = 0.07), and lower HDL-C (p = 0.07) Results showed for the first time that among youth with obesity, carriers of the Val66Met BDNF Met-alleles exhibited significantly higher C-reactive protein and energy intake in the form of fat and protein compared to Val-allele carriers, thereby providing support for the possible role of BDNF in appetite, weight, and metabolic regulation during adolescence. Clinical Trial Registration:http://clinicaltrials.gov/, identifier NCT00195858.